CCL-11 or Eotaxin-1: An Immune Marker for Ageing and Accelerated Ageing in Neuro-Psychiatric Disorders - Mariya Ivanovska; Zakee Abdi; Marianna Murdjeva; Danielle Macedo; Annabel Maes; Michael Maes (MDPI AG, 2020)
Background: CCL-11 (eotaxin) is a chemokine with an important role in allergic conditions. Recent evidence indicates that CCL-11 plays a role in brain disorders as well. This paper reviews the associations between CCL-11 and aging, neurodegenerative, neuroinflammatory and neuropsychiatric disorders. Methods: Electronic databases were searched for original articles examining CCL-11 in neuropsychiatric disorders. Results: CCL-11 is rapidly transported from the blood to the brain through the blood-brain barrier. Age-related increases in CCL-11 are associated with cognitive impairments in executive functions and episodic and semantic memory, and therefore, this chemokine has been described as an "Endogenous Cognition Deteriorating Chemokine" (ECDC) or "Accelerated Brain-Aging Chemokine" (ABAC). In schizophrenia, increased CCL-11 is not only associated with impairments in cognitive functions, but also with key symptoms including formal thought disorders. Some patients with mood disorders and premenstrual syndrome show increased plasma CCL-11 levels. In diseases of old age, CCL-11 is associated with lowered neurogenesis and neurodegenerative processes, and as a consequence, increased CCL-11 increases risk towards Alzheimer's disease. Polymorphisms in the CCL-11 gene are associated with stroke. Increased CCL-11 also plays a role in neuroinflammatory disease including multiple sclerosis. In animal models, neutralization of CCL-11 may protect against nigrostriatal neurodegeneration. Increased production of CCL-11 may be attenuated by glucocorticoids, minocycline, resveratrol and anti-CCL11 antibodies. Conclusions: Increased CCL-11 production during inflammatory conditions may play a role in human disease including age-related cognitive decline, schizophrenia, mood disorders and neurodegenerative disorders. Increased CCL-11 production is a new drug target in the treatment and prevention of those disorders.